Viscum album ssp. Investigation of In Vitro Antifungal Activity of Mistletoe (Viscum album ssp.) Living on Almond Tree (Prunus dolcis sp.): Investigation of In Vitro Antifungal Activity of Mistletoe - ÖNER, Fethi Ahmet; ALTINOK, Mahmut Alper; Aksoy, Aziz; Açıkgöz, Oğuzhan (Utan Kayu Publishing, 2024)
Mistletoe lives as a semi-parasite on the almond tree (Prunus dolcis) within the borders of Hac?lar district of Kayseri province; by obtaining leaf plant extracts of (Viscum album ssp. album), Fusarium moniliforme and Fusarium oxysporum f. sp. Control and experimental groups were prepared to investigate the antifungal activity against melongenae. Dose-1 extracts prepared as 10mg/ml and Dose-2 extracts prepared as 20mg/ml were applied. Two application doses and a control group were applied for fungal pathogens in 6 replicates. In the control group, sterile distilled water was added. Mixed potato dextrose agar (PDA) containing plant extract was prepared as media. According to the Tukey/Kramer Test, different doses of V. album ssp. album extract were found to detect F. oxysporum f. sp. The effect on the development of Fusarium melongenae and Fusarium moniliforme was compared. Dose-1 and Dose-2 have a significantly higher F. oxysporum, f. sp. F. melongenae, and Fusarium moniliforme effect on colony development than the control. It was also examined whether there was a difference in effect between the two fungi, and it was observed that V. album ssp. album extract had similar effects on both fungal species. Statistical results (p< 0001) were significant at both doses. In conclusion, It was determined that mistletoe leaf extracts showed antifungal activity against both fungal species at Dose-1 and Dose-2 rates.